1997
DOI: 10.1074/jbc.272.51.32025
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic Pyridoxine-β-d-Glucoside Hydrolase from Porcine Jejunal Mucosa

Abstract: During studies of the nutritional utilization of pyridoxine 5-␤-D-glucoside, a major form of vitamin B6 in plants, we detected two cytosolic ␤-glucosidases in jejunal mucosa. As expected, one was broad specificity ␤-glucosidase that hydrolyzed aryl ␤-D-glycosides but not pyridoxine ␤-D-glucoside. We also found a previously unknown enzyme, designated pyridoxine-␤-D-glucoside hydrolase, that efficiently hydrolyzed pyridoxine ␤-Dglucoside. These were separated and purified as follows: broad specificity ␤-glucosid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Studies on β -glucosidases have been carried out from different sources, namely, microbes, plants, and animals [7–14]. Amongst these, fungal sources are immensely explored due to their better prospects in commercial applications.…”
Section: Biotechnological Applications Of β-Glucosidasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on β -glucosidases have been carried out from different sources, namely, microbes, plants, and animals [7–14]. Amongst these, fungal sources are immensely explored due to their better prospects in commercial applications.…”
Section: Biotechnological Applications Of β-Glucosidasesmentioning
confidence: 99%
“…The specificity of β -glucosidases is variable towards different substrates depending on the enzyme source. The enzyme is ubiquitously present in nature and found in bacteria [7], fungi [8], yeasts [9], plants [1013], and animals [14], respectively. …”
Section: Introductionmentioning
confidence: 99%
“…The published method shows separate quantification of PN, PL, PM, and PNG (3). The nutritional availability of PNG in the human body is controversial (4). …”
mentioning
confidence: 99%
“…Cytosolic PNG hydrolysis was also reported to be inversely related to vitamin B 6 nutritional status in rodents (13,14). To further study cytosolic PNG hydrolysis, this laboratory purified BS␤G from pig intestinal mucosa, which led to the identification and subsequent purification of a distinct and novel cytosolic ␤-glucosidase, designated pyridoxine-5Ј-␤-D-glucoside hydrolase (PNG hydrolase) (15). It was found that PNG hydrolase, not BS␤G, was responsible for the cytosolic cleavage of PNG.…”
mentioning
confidence: 99%
“…It was found that PNG hydrolase, not BS␤G, was responsible for the cytosolic cleavage of PNG. Partial characterization of cytosolic PNG hydrolase revealed its ability to hydrolyze PNG as well as lactose and cellobiose but not sucrose (15). Partial amino acid analysis showed substantial sequence homology but revealed significant differences between PNG hydrolase and the brush border membrane enzyme lactase phlorizin hydrolase (LPH) (EC 3.2.1.23, EC 3.2.1.62, and EC 3.2.1.108) (16,17), the enzyme primarily responsible for the hydrolysis of dietary lactose.…”
mentioning
confidence: 99%